Natural Products on Nonalcoholic Fatty Liver Disease - Xu, Jiao-Ya; Zhang, Li; Li, Zhong-Ping; Ji, Guang (Current Drug Targets, 2015)
Non-alcoholic fatty liver disease (NAFLD) is a chronic disorder of lipid and carbohydrate metabolism and is often associated with endoplasmic reticulum stress, energy homeostasis dysregulation, and inflammation at cellular and molecular levels. Use of currently available anti-hyperlipidemia, hypoglycemia, or anti-inflammation drugs to treat NAFLD has not achieved desirable outcomes. A growing attention thus has been paid towards natural products as an alternative means in treating NALFD. Some of the natural products apparently possess the properties of ameliorating symptoms of NAFLD through restoration of lipid and carbohydrate metabolism and energy homeostasis. Data from recent animal and human studies concerning the use of natural products in the treatment of NAFLD are analyzed, and the potential underlying mechanisms are discussed.
Keywords: Natural products